2020
DOI: 10.3389/fmolb.2020.00159
|View full text |Cite
|
Sign up to set email alerts
|

Complex Destabilization in the Mitochondrial Chaperonin Hsp60 Leads to Disease

Abstract: Several neurological disorders have been linked to mutations in chaperonin genes and more specifically to the HSPD1 gene. In humans, HSPD1 encodes the mitochondrial Heat Shock Protein 60 (mtHsp60) chaperonin, which carries out essential protein folding reactions that help maintain mitochondrial and cellular homeostasis. It functions as a macromolecular complex that provides client proteins an environment that favors proper folding in an ATP-dependent manner. It has been established that mtHsp60 plays a crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 87 publications
(154 reference statements)
1
15
0
Order By: Relevance
“…Thus, a reduction in MDA-protein adduct formation may suggest a protective effect of CBD against the 60 kDa chaperonin. Such action of CBD can promote the maintenance of mitochondrial and cellular keratinocyte homeostasis [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a reduction in MDA-protein adduct formation may suggest a protective effect of CBD against the 60 kDa chaperonin. Such action of CBD can promote the maintenance of mitochondrial and cellular keratinocyte homeostasis [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies demonstrated that depletion of HSPD1 weakened radio-resistance in ESCC cells with ectopic expression HNF1A. There were evidences that HSPD1 is involved in maintaining normal protein homeostasis and protein denaturation repair (9,25). We speculated that HSPD1 was consumed with modifying new abundant proteins which maintain cell function after ectopic expression of HNF1A.…”
Section: Discussionmentioning
confidence: 96%
“…Heat shock 60kDa protein 1 (HSPD1) was a member of the heat shock protein family, also known as HSP60. HSPD1 assisted in maintaining protein homeostasis, participated in safeguarding mitochondrial function and intracellular homeostasis, and protected cardiomyocytes from apoptosis after its overexpression (8,9). Post-translational modi cation of HSPD1 resulted in different biological functions, such as in ammation, autoimmunity, carcinogenesis, cell replication and so on (10).…”
Section: Introductionmentioning
confidence: 99%
“…HSP60, also known as HSPD1, is a 60 kDa chaperone primarily found in the mitochondrial matrix [ 12 ]. The folding activity of HSP60 protects mitochondria from proteotoxicity under various types of stress [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%